FAKTOR RISIKO KEJADIAN PNEUMONIA PADA ANAK USIA 12-48 BULAN (Studi di Wilayah Kerja Puskesmas Gombong II Kabupaten Kebumen Tahun 2017) - Ratnaningtyas Ayu Mardani; Siti Fatimah Pradigdo; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2018)
The findings of pneumonia cases in Kebumen in 2016 as many as 764 cases per 10,000 children under five, where the highest incidence of cases in Puskesmas Gombong II, which is 508 cases. The purpose of this study was to determines the risk factors of pneumonia in children aged 12-48 months in Puskesmas Gombong II in 2017. This study is a descriptive study analitic using case control approach. The research subject as many as 80 children aged 12-48 months consisting of 40 cases and 40 controls taken through criteria inclusion, were analyzed by chi-square test and yates correction. The data were obtained from a questionnaire related to gender, a history of low birth weight, immunization history, nutritional status, history of exclusive breastfeeding, family smoking, and the density of residential living. The results showed the seven risk factors were examined three of them are risk factors for pneumonia, sex (p=0,014; CI=1,234-7,706; OR=3,095), history of exclusive breastfeeding (p=0,014; CI=1,247-7,781; OR=3,115), and the population density (p=0,003; CI=1,598-11,093; OR=4,210), whereas the other four is not a risk factor such a history of low birth weight (p=0,356; CI=0,462-40,608; OR=4,333), history of immunization (p=0,671; CI=0,364-12,240; OR=2,111), nutrition status (p=0,176; CI=0,625-10,950; OR=2,616), and family smoking (p=0,098; CI=0,856-5,742; OR=2,217). Despite smoking inside the house (p=0,012; CI=1,291-11,057; OR=3,778) and near by children (p=0,002; CI=1,787-20,147; OR=6,000) are counted as risk factors of pneumonia. This study recommends to be more intense for Puskesmas Gombong II in educating the citizens related to what is meant of pneumonia and the risk factors.